Differential effects of size-specific particulate matter on emergency department visits for respiratory and cardiovascular diseases in Guangzhou, China. (December 2018) - Ge, Erjia; Lai, Kefang; Xiao, Xiong; Luo, Ming; Fang, Zhangfu; Zeng, Yanjun; Ju, Hong; Zhong, Nanshan
Abstract: Background: Studies differentiating the cardiorespiratory morbidity effects of PM2.5, PM10, and PM2.5∼10 (i.e. coarse PM or PM c ) are still limited and inconsistent. Objective: To estimate the acute, cumulative, and harvesting effects of exposure to the three size-specific PM on cardiorespiratory morbidity, and their concentration-response relations. Methods: A total of 6, 727, 439 emergency department (ED) visits were collected from 16 public teaching hospitals in Guangzhou, from January 1st 2012 to December 31st 2015, among which over 2.1 million were asthma, COPD, pneumonia, respiratory tract infection (RTI), hypertension, stroke, and coronary heart disease (CHD). Distributed lag non-linear models (DLNM) was used to estimate the associations between the three size-specific PM and ED visits for the cardiovascular diseases. Long-term trends, seasonality, influenza epidemics, meteorological factors, and other gas pollutants, including SO2, NO2, and O3, were adjusted. We stratified the analyses by gender and age. Results: Elevated PM2.5 and PM10 were significantly associated with increased ED visits for pneumonia, RTI, and CHD at both lag0 and lag0-3 . A 10 μg/m 3 increment of PM c (at lag0-14 ) was estimated to increase ED visits for pneumonia by 6.32% (95% CI, 4.19, 8.49) and for RTI by 4.72% (95% CI, 3.81, 5.63), respectively. PM c showed stronger cumulative effects on asthma in children than elderly. We observed significant harvesting effects (i.e. morbidity displacements) of the three size-specific PM on respiratory but very little on cardiovascular ED visits. The concentration-response curves suggested non-linear relations between exposures to the three different sizes of PM and respiratory morbidity. Conclusions: Overall, the three size-specific PM demonstrated distinct acute and cumulative effects on the cardiorespiratory diseases. PM2.5 and PM c would have significant effects on pneumonia and RTI. Strategies should be considered to further reduce levels of ambient PM2.5 and PM c . Graphical abstract: Image 1 Highlights: PM2.5 and PM10 caused significant acute effects on pneumonia, RTI, and CHD. PM c had significant cumulative effects on bacteria-induced respiratory diseases. Long-term exposure to PMc caused higher effects on asthma in child than elderly. PM2.5, PM10, and PM c demonstrated strong harvesting effects on respiratory diseases. Relations between PM exposures and respiratory morbidity was non-linear. Abstract : This study gave a relatively complete understanding for the impacts of ambient particulate matter on cardiorespiratory morbidity, which provided valuable information and evidence to further limit levels of ambient particle matter and achieve better cardiorespiratory preventions.